2022
DOI: 10.1016/j.jbc.2021.101482
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic tau released from lung microvascular endothelial cells upon infection with Pseudomonas aeruginosa promotes neuronal tauopathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 50 publications
(76 reference statements)
0
29
0
Order By: Relevance
“…For example, RNAseq studies from the Betsholtz lab in mice 2 ( He et al, 2018 ; Vanlandewijck et al, 2018 ) and from the Human Protein Atlas in humans show that MAPT gene is expressed in lung endothelial cells. We recently confirmed that tau is indeed expressed in lung capillary endothelial cells, is released in response to P. aeruginosa infection, and is able to seed neuronal tau ( Choi et al, 2021 ).…”
Section: The Battle Between Humans and Germsmentioning
confidence: 73%
See 2 more Smart Citations
“…For example, RNAseq studies from the Betsholtz lab in mice 2 ( He et al, 2018 ; Vanlandewijck et al, 2018 ) and from the Human Protein Atlas in humans show that MAPT gene is expressed in lung endothelial cells. We recently confirmed that tau is indeed expressed in lung capillary endothelial cells, is released in response to P. aeruginosa infection, and is able to seed neuronal tau ( Choi et al, 2021 ).…”
Section: The Battle Between Humans and Germsmentioning
confidence: 73%
“…Strikingly, several studies have shown that toxic tau is transmissible ( Clavaguera et al, 2009 , 2013 ; Nonaka et al, 2010 ), leading to the idea that progression of the diverse but characteristic tau pathologies occurs through prion-like seed-dependent aggregation ( Hasegawa, 2016 ; Goedert and Spillantini, 2017 ). Importantly, transmissible tau can be generated not only in the brain but also by peripheral organs in response to an infection, including lung endothelial cells ( Balczon et al, 2013 , 2017 , 2019 ; Choi et al, 2021 ), and has been shown to reduce dendritic spine density ( Scott et al, 2020 ), impair learning and memory ( Balczon et al, 2019 ), and cause neuronal tauopathy ( Choi et al, 2021 ). The role of peripheral infections or inflammation leading to brain tau tangles is an understudied and vital area of research.…”
Section: An Accelerated Historical Perspective Of Alzheimer’s Disease...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when exposed to virulent clinical bacterial strains, including bacteria such as Pseudomonas aeruginosa , Klebsiella pneumoniae , and Staphylococcus aureus , the amyloids produced by lung endothelium become cytotoxic. In addition to Aβ, lung endothelium also produces several tau isoforms that are also released upon bacterial infection ( Balczon et al, 2017 ; Choi et al, 2021 ).…”
Section: Vascular Risk Factors Linked To Alzheimer’s Diseasementioning
confidence: 99%
“…Intriguingly, virulent bacteria-elicited lung endothelial Aβ and tau gain tropism toward the brain (i.e., neurotropic), are neurotoxic to brain cells, and may cause Aβ and tau aggregation ( Choi et al, 2021 ). Thus, a bacterial lung infection that elicits the release of endothelial Aβ and tau may induce incident dementia indirectly by triggering the senile plaques and/or NFT pathways ( Lin et al, 2018 ; Balczon et al, 2019 , 2021 ; Scott et al, 2020 ).…”
Section: Vascular Risk Factors Linked To Alzheimer’s Diseasementioning
confidence: 99%